Algoritmo De Segurança Na Clipagem De Aneurismas Cerebrais - Machado Filho, Mario Alberto Santana [UNIFESP] (2018)
Introduction: Cerebral aneurysms emerge from a branch of the main artery. Surgical clipping is the most definitive treatment for intracranial aneurysms and its aim is to achieve complete aneurysmal occlusion without compromising the lumen of a parent vessel or perforators, and with minimal brain tissue trauma. Neuroendoscopy’s relevance to check the aneurysm clipping and it’s safety contribution. Objective: To elaborate a safe algorithm for intracranial aneurysms clipping. Method: The study was approved by the Ethics and Research Commitee and inserted at Plataforma Brasil. The method Design Thinking was used through 4 stages: discovery, definition, development and delivery. Discovery: A literature research was done about the keywords: Protocol, Intracranial Aneurysm, Neuroendoscopy, Ultrasonography Doppler Transcranial, Cerebral Angiography, Algorithns. Surgeries were performed at Conjunto Hospitalar de Sorocaba (CHS) to obtain step by step images until the surgical clipping. With this data, questions were formulated to CHS´s neurosurgeons. Definition: The main problems relating to the intracranial aneurysm clipping were defined. Developing: Brainstorming with the CHS neurosurgeon´s team to find tools that were aimed to solve problems. It was proposed to use the neuroendoscope in the surgeries in order to lower the rate of complications. Delivery: To create an safe algorithm in order to secure a more effective clipping of intracranial aneurysm. Conclusion: A security algorithm was developed for clipping of intracranial aneurysms.